IMPLEMENTASI VARIASI METODE PADA MATA PELAJARAN AQIDAH AKHLAK DI MA MIDANUTTA’LIM JOGOROTO JOMBANG - Rizki Irwanto; Solihul Anshori (JURNAL ILMIAH NUSANTARA, 2025)
Variation method is a teaching method that uses more than one method. This variation method is very helpful in the learning process, especially in Islamic religious education subjects, because according to the teacher of the Aqidah Akhlak subject at MA Midanutta'lim Jogoroto Jombang. when using this method in the learning process, the material is centralized and focused on the teacher. However, in this case, students do not only listen, but in the middle of the learning process the teacher interacts with students by asking questions when the teacher has finished explaining the material. Based on the results of the research and discussion that have been presented previously, the following conclusions can be drawn: The application of a variety of methods in Islamic religious learning has a positive impact on students' interest, involvement, and understanding. To maximize the results, it is important to continue to improve supporting facilities, teacher training, and time and class management so that Islamic religious learning is more effective and enjoyable for students. Significant supporting factors in this study include support from the school, active teacher involvement, and high student interest in variations in learning methods. Meanwhile, the main inhibiting factors are related to time constraints, classroom management, limited facilities, and resistance to change faced by some teachers and students. To maximize the application of a variety of methods in Islamic religious learning, more efficient time management is needed.